Intelligent "Internet Plus" services in the first case of home hemodialysis in mainland China. Issue 4 (14th June 2021) - Ni, Zhaohui; Zhou, Yijun; Lu, Renhua; Shen, Jianxiao; Zhao, Li; Jin, Haijiao; Zhang, Haifen; Zhang, Bin; Li, Zhenyuan; Fang, Yan; Fang, Wei; Wang, Qin; et al.
Abstract: Background: Many studies have shown that compared with those who use other dialysis modalities, patients using home hemodialysis (HHD) have an increased rate of survival and better quality of life. It was noted in 2006 that there was opportunity for significant expansion of the use of HHD in many countries. China covers a vast area and has a large amount of end‐stage renal failure patients. But in mainland China, all dialysis treatments are in‐center, and the number of HHD patients is zero. In 2018, our hospital received the permission of the Shanghai government to carry out HHD. Case presentation: We initiated four incident hemodialysis patients on an HHD regimen, one patient has been dialyzed in the home safely for 8 months. The biochemical parameters of the first patient remained stable on the regimen and he achieved standard Kt / V urea targets. Treatment‐related adverse events were not reported during the follow‐up. We combined HHD with intelligent "Internet Plus" real‐time remote monitoring and introduced the Internet, especially visualization software, to replace traditional telephone and home visit methods. It is more intuitive and quicker to assist patients in performing home hemodialysis and improve the safety of treatment. Conclusions: HHD can be performed by selected trained patients in mainland China. Combined with the internet, visualization software, and traditional telephone and home visits, it is intuitive and quick to assist patients in carrying out HHD and improve the safety of treatment. HHD broadens the choices for uremia patients in China.